Remembering Whitney my story of love, loss, and the night the music stopped - Houston, Cissy 1933-2024; Dickey, Lisa (Harper, 2013)
The Grammy Award-winning American soul and gospel singer and mother of Whitney Houston reflects on her daughter's life, the events that led up to her death and the aftermath of a senseless tragedy
Includes discographies (p. 287-292) and index
Keywords: Houston, Cissy; Houston, Whitney; Houston, Whitney -- 1963-2012; Houston, Cissy -- 1933-2024; Singers / United States / Biography; Women singers / United States / Biography; African American women singers / United States / Biography; USA; Biografie